An Analysis of Unmarked Islamic Urdu Literature (Al-Qamar, 2022)
The study of non-dotted literature highlights its demanding and interesting nature, as authors sacrifice their time and effort to complete complex tasks and provide the world with a deeper understanding of literature. This type of work requires a mastery of language and an extensive vocabulary, making it difficult for the general public to fully comprehend. The authors who write non-dotted literature are believed to possess special blessings from Allah. The research also reveals that non-dotted literature is a tradition that persists even in the present day, with many people actively engaged in its creation. However, the industry is stagnant, with more dotted books than non-dotted or unmarked books in comparison to prose. This study suggests that the creation of non-dotted literature is an arduous task that requires immense dedication and skill, making it a niche genre that only a select few can excel in. The lack of growth in the industry may be attributed to the challenges faced by authors in creating non-dotted literature, as well as the limited audience that can appreciate its complexity. The research highlights that the non-dotted literature is a demanding and specialized genre that requires exceptional talent and effort to produce. While it may not be widely accessible to the general public, its continued existence and popularity among a select group of writers and readers demonstrate its enduring appeal.
Keywords: Unmarked; Urdu; Islamic Literature; Analysis